Ni supported on the CaO modified attapulgite as catalysts for hydrogen production from glycerol steam reforming. (18th March 2020) - Feng, P.; Huang, K.; Xu, Q.; Qi, W.; Xin, S.; Wei, T.; Liao, L.; Yan, Y.
Abstract: The Ni catalyst supported on CaO-modified attapulgite (CaO-ATP) were synthesized by wet impregnation method at a constant Ni metal loading (10 wt%). The catalyst was tested by carrying out a glycerin steam reforming reaction under the following conditions: 400–800 °C, W/G is 3, GHSV is 1 h −1 . Ni–CaO-ATP exhibited the highest hydrogen yield (85.30%) and glycerol conversion (93.71%) at 600 °C. The catalysts were characterized by N2 adsorption/desorption, BET, XRD, H2 -TPR, TG and SEM. The results show that ATP has good resistance to carbon deposition. As an attapulgite modifier of Ni–CaO-ATP, CaO promotes the dispersion of the active component nickel species, which would promote the water gas shift reaction, leading to the improving of hydrogen yield. In addition, the addition of Ca would further enhance the inhibition of carbon deposition and prolong the life of the Ni–CaO-ATP catalyst. Highlights: Ni–CaO-ATP exhibits the highest glycerol conversion and hydrogen yield. Attapulgite (ATP) has good carbon deposition resistance. CaO increases the activity of catalyst and the inhibition of carbon deposition.